Persepsi Keberlanjutan Petani Dalam Pemilihan Varietas Padi Unggul Mekongga - Rahmi Agustina; Miranda Romaully Br Sitanggang; Rum van Royensyah (Rawa Sains: Jurnal Sains STIPER Amuntai, 2024)
This study aims to determine: (1) Farmers‘ perception of sustainability in the selection of superior Mekongga rice varieties (cognitive, affective and conative) and (2) The difference in farmers’ income before and after using mekongga rice seed varieties. This research was conducted in Durian Gantang Village, Labuan Amas Selatan District, Hulu Sungai Tengah Regency. The research method used a survey using a questionnaire to collect sustainability perception data from 105 farmers who used Mekongga varieties with Likert Scale data analysis. Farmers' income data before and after using this rice variety Mekongga was also collected and analysed using the independent t-test. Farmers' perception of sustainability in the selection of superior rice variety Mekongga in Durian Gantang Village, Labuan Amas Selatan Sub-district, Hulu Sungai Tengah Regency is in the Good category. Cognitive components with good criteria, affective components with good criteria and conative components with good criteria. This shows that farmers have a positive perception in the selection of superior Mekongga rice varieties to support agricultural sustainability. In addition, there is a significant difference in farmers' income before and after using the Mekongga variety (sig 0.000 <0.05). The average income of farmers before using the Mekongga variety was Rp. 5,848,547.62 to Rp. 6,873,233.33 after using the Mekongga variety, with an average increase of Rp. 1,024,685.71 per one harvest. This shows that the use of Mekongga rice variety can contribute positively to the farmers' economy.